Return of the spider [large type] - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2025)
"The suspense classic Along Came a Spider introduced an unsurpassed rivalry: Detective Alex Cross, the 'human superhero' (New York Times) versus Gary Soneji, the 'most deliciously wicked character since Hannibal Lecter' (Lexington Herald-Leader). But that wasn't their first meeting. Police discover that Soneji kept a murder book, Profiles in Homicidal Genius, detailing his transformation from substitute teacher to hardened serial killer--including clues that imply missteps that Alex Cross may have made a rookie homicide detective. Now Alex must retrace the steps of that long-ago investigation and face the return of the spider"--